Epidemiology of cutaneous melanoma and keratinocyte cancer in white populations 1943–2036. (July 2021) - Garbe, Claus; Keim, Ulrike; Gandini, Sara; Amaral, Teresa; Katalinic, Alexander; Hollezcek, Bernd; Martus, Peter; Flatz, Lukas; Leiter, Ulrike; Whiteman, David
Abstract: Objectives: Cutaneous melanoma (CM) and keratinocyte cancer (KC) cause considerable morbidity and mortality. We analysed long-term trends of CM and KC in different white populations. Material and methods: Age-standardised (European Standard Population 2013) incidence and mortality rates (ASIR, ASMR) of CM were extracted from cancer registries in Denmark, New Zealand and the US SEER-Database. ASIRs of KC were sourced from registries of the German federal states Saarland and Schleswig–Holstein, and from Scotland. Age-period-cohort models were used to project melanoma incidence trends. Results: In Denmark between 1943 and 2016, melanoma ASIR increased from 1.1 to 46.5 in males, and from 1.0 to 48.5 in females, estimated to reach 60.0 and 73.1 in males and females by 2036. Melanoma mortality in Denmark (1951–2016) increased from 1.4 to 6.7 (males) and 1.2 to 3.7 (females). In New Zealand between 1948 and 2016, ASIR increased from 2.7 to 81.0 (males) and from 3.8 to 54.7 (females), slight declines are estimated by 2036 for both genders. Melanoma mortality increased six-fold in New Zealand males between 1950 and 2016; smaller increases were observed in females. We observed three- to four-fold increases in melanoma incidence in US whites, predicted to rise to 56.1 and 36.2 in males and females until 2036. Melanoma mortality also increased among US whites between 1970 and 2017, female melanoma mortality remained stable. Similar trends are shown for KC. Conclusions: In white populations, incidence of CM and KC significantly increased. CM incidence continues to rise in the short term but is predicted to decline in future. Highlights: Cutaneous melanoma (CM) incidence 73 years of observation and 20 years of projection. Incidence increase of CM 15–48 times. Similar trends in keratinocyte cancer. Age standardised with European standard population 2013 instead of crude rates.